Anticipated Negative Impact of Dobbs v. Jackson Women's Health Organization Among Young Adult Black Women in the US - Aaliyah Gray; Shelly Sinclair; Mary Jo Trepka; Kimberly M. Nelson (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Purpose The United States Supreme Court case Dobbs v. Jackson Women's Health Organization overruled federal protections for abortion in 2022. Young adult Black women (YABW) are expected to be among those most impacted directly by abortion restrictions and indirectly by effects on broader sexual and reproductive health access. This study assessed the extent to which this population anticipates negative impacts of the ruling. Methods A nationwide convenience sample of 500 YABW 18–22 years participated in an online sexual and reproductive health survey in November–December 2023. Participants rated the extent to which they anticipated negative impacts of Dobbs on five domains: their sex life and decisions related to prescription contraception, emergency contraception, sexually transmitted infection testing, and abortion. We used multivariable analyses including ordinal logistic regression to examine participant characteristics associated with anticipated negative impacts. Results Half of participants (51%–59%) anticipated at least some negative impact of the Dobbs ruling across the five domains, and 19% reported high levels of anticipated negative impact. Greater odds of a high anticipated impact score were associated with awareness of the Supreme Court decision prior to participation (aOR = 2.00, 95% CI [1.09–3.83]) and medical mistrust (aOR = 1.71, 95% CI [1.22–2.40]). Discussion These findings can inform the development of targeted support for YABW in the post‐ Dobbs landscape, which may include education on reproductive care options that remain legally available and culturally responsive care that fosters patient trust in the health care system within the current policy environment.